Stress, Coping, and Suicidal Ideation in College Students - Zastrow, Adam; Collura, Alyssa; Zellhoefer, Ashley S.; Nemec, Alicia; Nelson, Andrea; Miller, Tory; Fletch, Jordan (My University, 2010)
Suicide continues to be the second leading cause of death among college students, yet little research has examined the relationship between stress, coping styles and suicidal ideation within this population. The current study tried to address this gap in the literature in order to better inform assessment of risks for suicide and university prevention efforts.
Color poster with text, table, and graphs.
Keywords: College students--Suicidal behavior; Posters; Stress (Psychology)--Research; Stress in youth; Adjustment (Psychology)--Research; Suicide--Psychological aspects; Suicide--Risk factors